Input control and random choice: Improving the selection process for journal articles - Margit Osterloh; Bruno S. Frey (University of Zurich, Department of Economics, 2011)
The process by which scholarly papers are selected for publication in a journal is faced with serious problems. The referees rarely agree and often are biased. This paper discusses two alternative measures to evaluate scholars. The first alternative suggests input control. The second one proposes that the referees should decide only whether a paper reaches a minimal level of quality. Within the resulting set, each paper should be chosen randomly. This procedure has advantages but also disadvantages. The more weight that is given to input control and random mechanism, the more likely it is that unconventional and innovative articles are published.
Keywords: A1; A10; D02; H83; L23; M50; 330; Bibliometrie; Statistische Methode